2000
DOI: 10.1097/00006454-200011000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of climate, ethnicity and socioeconomic status to Kawasaki disease in San Diego County, 1994 through 1998

Abstract: KD is a common childhood vasculitis of unknown etiology. The skewed ethnic distribution and seasonality are consistent with the hypothesis that KD is an infectious disease that is influenced by environmental and genetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 19 publications
1
53
1
2
Order By: Relevance
“…It is speculated that such regional variation in the seasonal pattern may be attributable to differences in the climate of these regions. In support of this, Bronstein et al 12 found the incidence of KD in San Diego correlates with temperature and rainfall. Future studies are needed to investigate the effect of climate on the epidemiology of KD.…”
Section: Discussionmentioning
confidence: 83%
“…It is speculated that such regional variation in the seasonal pattern may be attributable to differences in the climate of these regions. In support of this, Bronstein et al 12 found the incidence of KD in San Diego correlates with temperature and rainfall. Future studies are needed to investigate the effect of climate on the epidemiology of KD.…”
Section: Discussionmentioning
confidence: 83%
“…10 These estimates are similar to those reported in smaller studies. 12,13 Recent reports have emphasized the occurrence of Kawasaki disease in older children, who may have a higher prevalence of cardiovascular complications related to late diagnosis. 14 -16 Rates of recurrence and familial occurrence of Kawasaki disease are best documented in the literature from Japan; these rates may be lower in other races and ethnicities.…”
Section: Epidemiologymentioning
confidence: 99%
“…10,11 Reported associations of Kawasaki disease with antecedent respiratory illness and exposure to carpet-cleaning fluids have not been consistently confirmed. 12,13,[27][28][29][30] Other factors that are reportedly associated with Kawasaki disease include having preexisting eczema, 31 using a humidifier, 30 and living near a standing body of water. 32 The case fatality rate in Kawasaki disease in Japan is 0.08%.…”
Section: Epidemiologymentioning
confidence: 99%
“…Siblings of KD patients have a 6-10-fold greater incidence than the general population [12], and KD-affected children are more likely to have parents who had the condition [13]. Other aspects of the epidemiological evidence, including seasonality and spatiotemporal clustering of cases, together with the clinical features, suggest an infectious aetiology [2,5,6,14,15]. The age distribution of KD cases is similar to that of many childhood infections [2].…”
Section: Introductionmentioning
confidence: 99%